Integrated composite positive electrode with solid electrolyte layer and its preparation method

Through dry process, integrated composite positive electrode sheet with solid electrolyte layer was prepared, and laser holes and highly conductive carbon materials were used to solve the challenges of liquid lithium-ion batteries in terms of energy density and safety, achieving efficient electricity Improved chemical performance and safety.

CN118867139BActive Publication Date: 2025-01-14SHENZHEN AUTOMOTIVE RES INST BEIJING INST OF TECH (SHENZHEN RES INST OF NAT ENG LAB FOR ELECTRIC VEHICLES)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411279188.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-14
Estimated Expiration
2044-09-12

Smart Images

  • Figure CN118867139B_ABST
    Figure CN118867139B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of battery material technology, and specifically relates to an integrated composite positive electrode sheet with a solid electrolyte layer and a preparation method thereof, wherein the preparation method comprises: premixing a conductive carbon material, oxide solid electrolyte particles and a positive electrode active material, adding a binder for low-temperature and low-speed dispersion after high-speed dispersion treatment, and performing supersonic airflow treatment after heat preservation treatment to obtain a fibrous powder, and preparing an electrode membrane by multi-stage hot rolling; preparing a solid electrolyte membrane by similar steps, stacking the two and performing hot rolling treatment to form an integrated composite positive electrode membrane, and finally compounding with a carbon-coated aluminum foil current collector to form a channel hole to obtain an integrated composite positive electrode sheet with a solid electrolyte layer. The present application solves the technical problem that the long electron and ion transmission path in thick electrodes, large interface impedance and poor adhesion lead to limited battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular, relates to an integrated composite positive electrode sheet with a solid electrolyte layer and a preparation method thereof. Background Art

[0002] The improvement of energy density and safety of liquid lithium-ion batteries has become a key driving force for the development of battery technology. Manufacturers and researchers are working hard to improve the performance of liquid lithium-ion batteries by developing new materials and optimizing battery systems, as well as improving battery structure design and manufacturing processes. However, existing technologies still face many challenges in achieving these goals.

[0003] In terms of safety optimization, the current main research direction is to eliminate the problem of poor thermal stability of the diaphragm by improving the diaphragm material in lithium-ion batteries. Traditional polyolefin diaphragms (such as polyethylene and polypropylene) are widely used in lithium-ion batteries due to their chemical stability and good processing properties. However, traditional polyolefin diaphragms have poor thermal stability and are prone to shrinkage and deformation when the battery experiences thermal runaway, resulting in direct contact between the positive and negative electrodes, causing internal short circuits, and further causing serious safety hazards such as battery combustion or explosion. To this end, many researchers have tried to replace traditional diaphragms by coating oxide solid electrolyte materials with high thermal stability on the surface of the electrode to improve the safety of the battery.

[0004] In terms of improving energy density, research has mainly focused on developing high-load thick electrodes and optimizing the overall structural design of the battery. However, the practical application of high-load thick electrodes is often accompanied by some technical difficulties. For example, as the thickness of the electrode increases, the diffusion path of lithium ions becomes longer, resulting in an increase in the lithium ion concentration gradient in the thickness direction of the electrode. In addition, the increase in compaction density will cause the pores to become smaller, making it difficult for the electrolyte to penetrate, thereby increasing the internal resistance of the battery. These problems may affect the electrochemical performance or volume energy density of the electrode while improving the energy density.

[0005] In order to overcome these challenges, solvent-free dry processes have received widespread attention in recent years. The dry process is to mix the positive electrode active material, conductive agent and solid binder and then fiberize them, and then press them into a self-supporting film by hot roller pressing and composite with the current collector. This method can not only effectively control the electrode thickness and the uniformity of thick electrodes, but also is particularly suitable for the preparation of ultra-high loading electrodes, which has the advantages of reducing costs and improving environmental friendliness. However, although the dry process has shown its potential in improving battery performance, there are still many problems that need to be solved in its practical application:

[0006] 1. Although the existing dry process can effectively control the thickness and uniformity of the electrode, it cannot simultaneously solve the problem of long electron and ion transmission paths and slow conduction speed inside the thick electrode. This problem leads to excessive polarization of the electrode piece, and the electrochemical performance of the electrode material cannot be fully utilized.

[0007] 2. The solid electrolyte layer is usually attached to the surface of the rolled electrode by coating or spraying. However, this method results in poor adhesion between the electrolyte layer and the electrode, loose contact between the electrolyte layer and the electrode, and an obvious interface layer, resulting in excessively high interface impedance.

[0008] 3. The existing dry process for preparing solid electrolyte membranes usually uses non-woven fabrics as porous substrates, and fills the solid electrolyte layer in the pores of the porous substrate to obtain a solid electrolyte membrane. Although the partial filling design can retain the porosity of the porous substrate and promote ion transmission, too many pores may cause discontinuity in the ion conduction path, affecting the overall conductivity of ions in the membrane, especially at high rate charge and discharge, the efficiency of ion transmission may be insufficient, resulting in a decrease in battery performance. Since the porous substrate is an independent structure, the solid electrolyte membrane prepared using this structure is a high-rigidity membrane. After being composited with the pole piece, it is difficult to adapt to the volume change and stress change of the battery during the charge and discharge process. The porous substrate will undergo mechanical deformation or pore structure changes in long-term cycles, thereby affecting the stability of the solid electrolyte layer, resulting in interface peeling or cracking between the membrane and the porous substrate. Long-term use may lead to performance degradation, thereby affecting the overall performance and life of the battery. In addition, the composite solid electrolyte membrane prepared by this method is relatively thick, which is not conducive to the infiltration of the electrolyte and ion transmission, affecting the performance of the battery's electrochemical performance, and greatly affecting the energy density of the battery cell.

[0009] 4. The existing dry process prepares the electrode membrane by hot rolling the mixed powder material and compounding it with carbon-coated aluminum foil. However, due to the poor adhesion between the electrode membrane and the current collector, the interface impedance is large and even film peeling may occur, which further affects the overall performance of the battery.

[0010] 5. With the increase of electrode thickness and the introduction of electrolyte layer, the wetting ability of electrolyte is seriously affected, and it is difficult to penetrate deep into the electrode plate, which prolongs the transmission path of lithium ions and reduces the transmission speed, thus seriously deteriorating the rate performance and cycle performance of the battery. Summary of the invention

[0011] In response to the above problems, the present invention provides an integrated composite positive electrode sheet with a solid electrolyte layer and a method for preparing the same, by constructing an integrated composite positive electrode membrane integrating a solid electrolyte and a high-load electrode, and after compounding it with a through-hole carbon-coated aluminum foil, an array-type vertical channel structure is precisely constructed on the electrolyte layer and the electrode membrane layer by laser pore making.

[0012] In one aspect, the present invention provides a method for preparing an integrated composite positive electrode sheet having a solid electrolyte layer, the preparation method comprising the following steps:

[0013] Step 1: premixing the conductive carbon material, oxide solid electrolyte particles of various particle sizes, and the positive electrode active material in a certain proportion to obtain a mixed material, and using a high-speed dispersion process to obtain a uniformly mixed first powder;

[0014] Step 2: adding a certain amount of binder to the first powder, dispersing the binder and the first powder under low temperature and low speed conditions to uniformly mix the binder and the first powder to obtain a second powder;

[0015] Step 3: heat-insulating the second powder at a certain temperature to obtain a pre-fiberized second powder;

[0016] Step 4: treating the heat-insulated second powder with a supersonic airflow to fiberize the binder in the second powder, and uniformly dispersing the conductive carbon material and oxide solid electrolyte particles of various particle sizes in the second powder, coating them on the outer surface of the positive electrode active material particles and incorporating them into the fiberized binder together, to obtain a third powder;

[0017] Step 5: subjecting the third powder to a multi-stage hot roller pressing process to obtain an electrode membrane;

[0018] Step 6: premixing the binder and the oxide solid electrolyte particles in a certain proportion, dispersing them under low temperature and low speed conditions to obtain a fourth powder, and treating the fourth powder according to steps 3-5 to obtain a solid electrolyte membrane;

[0019] Step 7: stacking the electrode membrane and the solid electrolyte membrane in a certain order and performing hot rolling treatment to obtain an integrated composite positive electrode membrane;

[0020] Step 8: stacking the integrated composite positive electrode film and the carbon-coated aluminum foil current collector and performing a hot rolling process, constructing channel holes on the integrated composite positive electrode sheet after hot rolling, and obtaining an integrated composite positive electrode sheet with a solid electrolyte layer;

[0021] The oxide solid electrolytes of various particle sizes in step 1 include at least two types of micron particles and nanoparticles; the oxide solid electrolytes in steps 1 and 6 include one or more of perovskite oxide solid electrolytes, garnet oxide solid electrolytes, and NASICON oxide solid electrolytes;

[0022] In step 8, laser pore making is performed and vertical channel holes are constructed from one side of the integrated composite positive electrode sheet having the solid electrolyte membrane toward the electrode membrane in an array distribution manner.

[0023] Furthermore, the depth of the channel hole is the sum of the thickness of the solid electrolyte membrane and the electrode membrane.

[0024] Furthermore, in step 6, the amount of the binder added is 1-7wt% of the mass of the solid electrolyte membrane, and the amount of the oxide solid electrolyte particles added is 93-99wt% of the mass of the solid electrolyte membrane.

[0025] Furthermore, in step 7, the solid electrolyte membrane is stacked and rolled in the order of being located above the electrode membrane, and in step 8, the integrated composite positive electrode membrane is stacked and rolled with one side of the electrode membrane being bonded to the carbon-coated aluminum foil current collector.

[0026] Furthermore, in step 8, an array-type through-hole structure is provided on the carbon-coated aluminum foil current collector.

[0027] On the other hand, the present invention provides an integrated composite positive electrode sheet with a solid electrolyte layer, wherein the integrated composite positive electrode sheet with a solid electrolyte layer is prepared by any of the preparation methods described above; it includes an integrated composite positive electrode membrane and an array-type through-hole carbon-coated aluminum foil current collector close to the integrated composite positive electrode membrane; the integrated composite positive electrode membrane includes a solid electrolyte membrane and an electrode membrane, and the solid electrolyte membrane and the array-type through-hole carbon-coated aluminum foil current collector are respectively composited on both sides of the electrode membrane.

[0028] Furthermore, the thickness of the solid electrolyte membrane is 10-60 μm.

[0029] Furthermore, the thickness of the integrated composite positive electrode plate is 30-500 μm, and the aperture of the channel hole of the integrated composite positive electrode plate is 5-500 μm.

[0030] The beneficial effects of the present invention are:

[0031] First, the present invention uses a dry process to prepare an oxide solid electrolyte film, and uses a precise rolling process to ensure the integrated composite of the film and the high-load electrode membrane. The same binder can achieve flexible contact between the electrolyte layer and the electrode layer, eliminate the interface gap, and greatly reduce the interface resistance between the electrolyte layer and the electrode layer. The solid electrolyte layer with high thermal stability replaces the commercial diaphragm with poor thermal instability, which significantly improves the overall safety of the battery. In order to further solve the problem that the electrolyte is difficult to effectively penetrate the solid electrolyte layer and the thick electrode membrane, the present invention introduces advanced laser pore-making technology to accurately construct an array-type through-hole structure on the integrated composite electrode sheet. This design not only optimizes the vertical channel layout, effectively reduces the tortuosity of the electrode electrode sheet, but also significantly improves the porosity. With the help of the capillary force of the vertical channel, the electrolyte can quickly and evenly infiltrate the entire electrode sheet, greatly accelerating the ion transmission efficiency, thereby ensuring the excellent performance of the battery cell under high-rate charging and discharging and long-term cyclic use, and solving the difficulty of simultaneously improving safety and energy density.

[0032] Second, the present invention cleverly combines micron- and nano-scale oxide solid electrolyte particles in the positive electrode layer, and achieves dual advantages through a carefully designed particle size matching strategy: small particles are closely attached to the surface of the positive electrode active material to form a protective layer and promote interface contact; large particles effectively shorten the ion transmission path, reduce the interface between particles, and significantly improve the migration rate of lithium ions inside the electrode, thereby comprehensively improving the electrochemical performance of the battery; in addition, in order to further optimize the electron transmission efficiency inside the thick electrode, the present invention innovatively uses high aspect ratio and high conductivity carbon materials. These carbon materials are uniformly and densely wrapped on the surface of the electrolyte particles, and a continuous and efficient conductive network is constructed by overlapping each other. This design greatly promotes the rapid transmission of electrons inside the electrode, ensuring the excellent electrochemical performance of the battery under high load conditions;

[0033] Third, the present invention is different from the existing technical solutions. It introduces a carbon-coated aluminum foil current collector with a special array-type through-hole structure. This current collector uses precise chemical or physical pore-making technology to process regular, orderly, distributed and arranged tiny through-holes on the surface of the aluminum foil to form an array structure to improve the performance of the current collector. The carefully designed through-hole structure not only serves as a "micro-anchor point" for the electrode membrane, but also greatly enhances the bonding force between the electrolyte membrane and the current collector through physical locking, effectively resists the mechanical stress generated during the battery charge and discharge cycle, and fundamentally solves the problem of membrane removal. The through-hole or microporous structure increases the specific surface area of ​​the current collector, provides more active sites for electrochemical reactions, and allows more electrolyte to penetrate deeply into the electrode membrane, improving the contact between the electrolyte and the electrode membrane, and solving the technical problems of poor adhesion and easy membrane removal between the dry electrode membrane and the current collector. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a flow chart of a method for preparing an integrated composite positive electrode sheet with a solid electrolyte layer of the present invention;

[0035] Figure 2 is a cross-sectional SEM image of an integrated composite positive electrode sheet with a solid electrolyte layer according to an embodiment of the present invention;

[0036] Figure 3 This is a SEM image of the channel hole of the integrated composite positive electrode sheet with a solid electrolyte layer according to an embodiment of the present invention;

[0037] Figure 4 Specific capacity-voltage curves of Example 1 and Comparative Example 1 of the present invention;

[0038] Figure 5 1 is a cycle performance curve diagram of Example 1 of the present invention and Comparative Example 1;

[0039] Figure 6 This is a cycle performance test diagram of a high surface capacity electrode sheet prepared by the process of Example 1 of the present invention;

[0040] Figure 7 is a comparison chart of discharge capacity retention rates of Example 1 of the present invention and Comparative Example 1 at different discharge rates (C rates);

[0041] Figure 8 It is a curve diagram of temperature and voltage of the battery cells in the acupuncture test of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0042] In order to enable those skilled in the art to better understand the technical solution of the present application, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0043] The terms such as up, down, left, right, front and back in this application document are based on the positional relationships shown in the drawings. If the drawings are different, the corresponding positional relationships may also change accordingly, so they cannot be understood as limiting the scope of protection.

[0044] In this application, the terms "install", "connected", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, an integral connection, a mechanical connection, an electrical connection, or mutual communication, a direct connection, or an indirect connection through an intermediate medium, the internal connection of two components, or the interaction relationship between two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0045] Refer to the instruction manual Figure 1 The present invention describes a method for preparing an integrated composite positive electrode sheet with a solid electrolyte layer. The specific steps of the preparation method are as follows:

[0046] Step 1: premix the conductive carbon material, oxide solid electrolyte particles of various particle sizes, and the positive electrode active material in a certain proportion to obtain a mixed material, and use high-speed dispersion to process the mixed material to obtain a uniformly mixed first powder.

[0047] Specifically, step 1 uses a powerful mixer, such as a high-speed dispersing device, to add the conductive carbon material, oxide solid electrolyte particles of various particle sizes, and positive electrode active materials to the high-speed dispersing device in a certain proportion, and utilizes the strong shear force of the high-speed dispersing device to break up and disperse the agglomerates of the conductive carbon material and the various oxide solid electrolyte particles, so that the conductive carbon material, oxide solid electrolyte particles of various particle sizes, and the positive electrode active materials are evenly mixed.

[0048] In step 1, the amount of conductive carbon material added is 1-6wt% of the mass of the electrode membrane, the amount of the mixture of oxide solid electrolyte particles of various particle sizes added is 1-10wt% of the mass of the electrode membrane, and the amount of positive electrode active material added is 77-96wt% of the mass of the electrode membrane.

[0049] The rotation speed of the high-speed dispersion in step 1 is 5000-10000 r / min, the stirring time of the mixed material is 30-300 min, and the mixing temperature is room temperature.

[0050] The conductive carbon material is a carbon material with a high aspect ratio and high conductivity. Preferably, the conductive carbon material is one or more of graphene, carbon nanotubes, and carbon nanofibers, but is not limited thereto.

[0051] The oxide solid electrolyte includes one or more of a perovskite oxide solid electrolyte, a garnet oxide solid electrolyte, and a NASICON ((Na+Site-Isolated CONductor)) oxide solid electrolyte, but is not limited thereto. Preferably, the perovskite oxide solid electrolyte is selected from lithium lanthanum titanium oxide; the garnet oxide solid electrolyte is selected from one or more of lithium lanthanum zirconium oxide, niobium-doped lithium lanthanum zirconium oxide, tantalum-doped lithium lanthanum zirconium oxide, and niobium-tantalum dual-doped lithium lanthanum zirconium oxide; the NASICON oxide solid electrolyte is selected from one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, and lithium yttrium titanium phosphate.

[0052] The oxide solid electrolytes of various particle sizes include at least micron particles and nanoparticles. Preferably, the particle size of the micron particles is in the range of 1-5 μm, the particle size of the nanoparticles is in the range of 100-600 nm, and the mixing ratio of the nanoparticles to the micron particles is in the range of 5:1-1:1.

[0053] It should be noted that the present invention does not limit the type of positive electrode active material. All commonly used positive electrode active materials in the art are suitable for the present invention, which may be doped positive electrode active materials, undoped positive electrode active materials, or coated modified positive electrode active materials.

[0054] The positive electrode active material is the main material of the first powder. Preferably, the positive electrode active material includes: lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2), lithium nickel cobalt aluminum oxide (LiNi x Co y Al 1-x-y O2), lithium iron phosphate (LiFePO4), lithium iron manganese phosphate (LiMn x Fe 1-x PO4), lithium manganese oxide (LiMnO2) and lithium cobalt oxide (LiCoO2), but not limited thereto.

[0055] Step 2: Add a certain amount of binder to the first powder, and use low temperature and low speed conditions to disperse and evenly mix the binder and the first powder to obtain a second powder.

[0056] Specifically, step 2 uses a powerful mixer, such as a high-speed dispersing device. On the basis of step 1, a certain amount of binder is added to the first powder of the high-speed dispersing device, the rotation speed of the high-speed dispersing device is reduced, and a smaller shear force is used to achieve uniform dispersion of the binder in the first powder. At the same time, the temperature of the stirring tank of the high-speed dispersing device is reduced, and stirring is performed within a certain stirring time to obtain the second powder. Since the binder is highly sensitive to temperature and shear force, the binder can be prevented from being prematurely fiberized in this process by low temperature and low speed. If the binder is fiberized prematurely, it is difficult for the binder to be uniformly dispersed in the first powder, resulting in excessive or insufficient local binder, which affects the strength of the electrode membrane.

[0057] The binder includes one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), polyacrylic acid (PAA), polyvinyl alcohol (PVA) and polyacrylonitrile (PAN), but is not limited thereto. Preferably, the binder is PTFE.

[0058] The amount of binder added in step 2 is 2-7wt% of the mass of the electrode membrane.

[0059] It should be noted that the binder is highly sensitive to temperature and shear force. If the binder is fiberized prematurely, it will be difficult to evenly disperse the binder in the first powder, resulting in excessive or insufficient binder in some parts, affecting the strength of the electrode membrane.

[0060] In step 2, the rotation speed of the high-speed dispersing device is 200-800 r / min, the mixing time of the binder and the first powder is 10-60 min, and the temperature of the mixing tank of the high-speed dispersing device is controlled at 0-10°C.

[0061] Step 3: The second powder is subjected to a heat preservation treatment at a certain temperature to obtain a pre-fiberized second powder.

[0062] Since the surface temperature of the second powder mixed at low temperature in step 2 is reduced, it cannot maintain sufficient fluffiness, which will lead to insufficient fiberization of the subsequent second powder. There is a risk of breakage and powder loss during subsequent rolling. Therefore, before the second powder is subjected to the fiberization process, the powder needs to be pre-fiberized to transform the binder crystals in the powder into a soft and fluffy state.

[0063] Specifically, step 3 uses a high-temperature oven, places the second powder in the high-temperature oven, and uses the high sensitivity of the binder to temperature to keep the second powder warm at a temperature of 90-200° C. for 2-10 h.

[0064] Step 4: Use supersonic airflow to treat the second powder after heat preservation, fiberize the binder in the second powder, and evenly disperse the conductive carbon material and oxide solid electrolyte particles of various particle sizes in the second powder, coat them on the outer surface of the positive electrode active material particles and incorporate them into the fiberized binder together to obtain a third powder.

[0065] Specifically, in step 4, a supersonic airflow pulverizer is used to perform fiberization treatment on the second powder:

[0066] The second powder after pre-fiberization is added to the supersonic airflow pulverizer, and compressed air is generated through the nozzle to generate a supersonic airflow that is injected into the pulverizing chamber. The supersonic airflow velocity is greater than 300 m / s, so that the second powder is fluidized. The accelerated second powder converges at the intersection of the jet airflows of several nozzles, generating violent collisions, frictions and shearing, so that the secondary agglomerated particles of the conductive carbon material and the oxide solid electrolyte particles of various particle sizes are fully crushed and dispersed, and a uniformly dispersed conductive agent and solid electrolyte coating layer are formed on the surface of the active material particles, thereby forming a good conductive and ion-conducting network. At the same time, under the action of strong shear force, the uniformly dispersed binder is fully fiberized to obtain a fluffy binder structure, so that the well-dispersed active material coated with conductive carbon and solid electrolyte is incorporated into the fiberization to obtain the third powder.

[0067] Step 5: Perform multi-stage hot rolling processing on the third powder to obtain an electrode membrane.

[0068] Specifically, step 5 is the electrode diaphragm manufacturing process, which is processed by a powder metering and conveying device and a multi-stage hot rolling equipment: the third powder is transmitted to the multi-stage hot rolling equipment through the powder metering and conveying device, and the working temperature of the heating roller is in the range of 150-250°C. During the multiple hot rolling processes, the fluffy third powder has binder fibers overlapping each other, extruded and moved to form a network structure, and the network structure wraps and bonds the other component particles together. After roller forming, hot pressing shaping, trimming and winding are carried out to complete the entire hot pressing forming process to form an electrode diaphragm with uniform thickness, and the diaphragm is wound up for standby use.

[0069] The working temperature of the heating roller in step 5 is within the range of 150-250°C, which can ensure that the binder can be fully fiberized under the action of roller pressure and high temperature, so that the fibers overlap each other, build a continuous binder fiber network, and ensure the mechanical strength of the electrode membrane. This step can achieve precise control of the thickness of the electrode membrane by controlling the roller gap and pressure of the multi-stage roller.

[0070] Step 6: premix the binder and the oxide solid electrolyte particles in a certain proportion, disperse them under low temperature and low speed conditions to obtain a fourth powder, and process the fourth powder according to steps 3-5 to obtain a solid electrolyte membrane.

[0071] In step 6, the amount of the binder added is 1-7wt% of the mass of the solid electrolyte membrane, and the amount of the oxide solid electrolyte particles added is 93-99wt% of the mass of the solid electrolyte membrane.

[0072] It should be noted that the particle size of the oxide solid electrolyte particles in step 6 may be a single particle size or a combination of multiple particle sizes, and may be adjusted according to actual needs.

[0073] Step 7: stack the electrode membrane and the solid electrolyte membrane in a certain order, and perform hot rolling treatment to obtain an integrated composite positive electrode membrane.

[0074] Specifically, the solid electrolyte membranes are stacked and rolled in the order that the solid electrolyte membranes are located above the electrode membranes.

[0075] Step 8: stack the integrated composite positive electrode membrane and the carbon-coated aluminum foil current collector and perform hot rolling treatment, construct channel holes on the integrated composite positive electrode sheet after hot rolling, and obtain an integrated composite positive electrode sheet with a solid electrolyte layer.

[0076] Specifically, the side of the integrated composite positive electrode membrane with the electrode membrane is laminated and stacked with the carbon-coated aluminum foil current collector, and hot rolling is performed. This step controls the compaction of the composite positive electrode sheet by adjusting the roll gap width and rolling pressure. Laser pore processing is used, and vertical channel holes are constructed from the side of the integrated composite positive electrode sheet with the solid electrolyte membrane to the electrode membrane in an array distribution manner. The depth of the channel hole is the sum of the thickness of the solid electrolyte membrane and the electrode membrane, which can achieve good infiltration of the electrolyte.

[0077] The laser pore making of the present invention adopts femtosecond laser technology, and by utilizing its excellent spatial resolution and fine processing capability, it can realize micro-scale processing on the surface of the pole piece, such as microchannel holes. The ultra-short pulse time of the femtosecond laser produces almost no thermal impact during the processing, which can avoid thermal damage and deformation to the pole piece and maintain the original quality and structure of the pole piece, which is superior to mechanical or chemical pore making technology.

[0078] The pore size of the channel hole of the integrated composite positive electrode plate is 5-500 μm. Further, the pore size of the channel hole of the integrated composite positive electrode plate is 5-50 μm.

[0079] The carbon-coated aluminum foil current collector in step 8 uses an array-type through-hole carbon-coated aluminum foil current collector, which is different from ordinary carbon-coated aluminum foil and aluminum foil current collectors. The surface of the array-type through-hole carbon-coated aluminum foil current collector of the present invention is processed by chemical or physical methods to form regularly arranged tiny through holes on the current collector to construct an array structure, which can increase the surface roughness of the current collector and effectively improve the adhesion between the electrode membrane and the current collector interface.

[0080] On the basis of the above steps 1-8, the prepared integrated composite positive electrode sheet, negative electrode sheet and electrolyte of the solid electrolyte layer are assembled to obtain the preparation of the battery cell.

[0081] The present invention also describes an integrated composite positive electrode sheet with a solid electrolyte layer, including an integrated composite positive electrode membrane and an array-type through-hole carbon-coated aluminum foil current collector close to the integrated composite positive electrode membrane, the integrated composite positive electrode membrane includes a solid electrolyte membrane and an electrode membrane, and the solid electrolyte membrane and the array-type through-hole carbon-coated aluminum foil current collector are respectively composited on both sides of the electrode membrane. Figure 2-3 , Figure 2 This is a cross-sectional SEM image of an integrated composite positive electrode sheet with a solid electrolyte layer prepared by the above preparation method. It can be seen from the figure that there is no interface gap between the solid electrolyte membrane and the electrode membrane in the integrated composite positive electrode sheet, indicating that a good composite is achieved between the two. The interface resistance between the electrolyte layer and the electrode layer can be greatly reduced through flexible and close contact. Figure 3This is a front SEM image of the integrated composite positive electrode. It can be seen from the image that after laser pore making treatment, an array of through-hole structure is constructed on the electrode.

[0082] The thickness of the solid electrolyte membrane is 10-60μm, and the thickness of the electrolyte membrane can be selected according to actual needs. For example: the thickness of the solid electrolyte membrane is 10μm, which is used for high-energy-density solid-state batteries, usually used in consumer electronic products (such as smart phones, laptops). The thickness of the solid electrolyte membrane is greater than 10μm and less than 50μm, and is used in scenarios with balanced performance and safety, such as electric vehicles, power tools, etc. The thickness of the solid electrolyte membrane is greater than 50μm and less than 60μm, which is suitable for solid-state battery scenarios requiring high safety and long life, such as energy storage systems, spacecraft power supplies, etc.

[0083] The thickness of the integrated composite positive electrode sheet with a solid electrolyte layer is 30-500 μm.

[0084] The compaction density of the high-load composite positive electrode plate with gradient is related to the positive electrode material used. Taking NCM811 battery as an example, the preset range of the compaction density of the plate is 2.8-3.8 g / cm 3 .

[0085] The integrated composite positive electrode sheet with a solid electrolyte layer of the present invention is applied to the fields of liquid lithium-ion batteries and semi-solid batteries. For liquid lithium-ion batteries, the solid electrolyte layer is composited on one side of the integrated composite positive electrode membrane, and its surface is in contact with the liquid electrolyte. The liquid electrolyte is located between the negative electrode and the solid electrolyte layer, which reduces the corrosion of the electrolyte on the positive electrode material. At the same time, a stable solid-liquid interface is formed between the positive electrode and the electrolyte, so that the liquid lithium-ion battery can have both the stability of the solid electrolyte and the high ion conductivity of the liquid electrolyte. The other side of the integrated composite positive electrode membrane has an array-type through-hole carbon-coated aluminum foil current collector, which can help disperse the current through its unique through-hole design, reduce the internal resistance of the current collector, improve ion conduction, and enhance the overall performance of the battery. For semi-solid-state batteries, an integrated composite positive electrode plate is used as the positive electrode. One side of the integrated composite positive electrode plate is a solid electrolyte layer. A stable solid-liquid or solid-gel interface is formed on the outside of the solid electrolyte layer. A small amount of liquid or gel electrolyte exists between the solid electrolyte layer and the negative electrode. The other side of the integrated composite positive electrode plate has the same structure as the liquid lithium-ion battery. The integrated composite positive electrode plate with a solid electrolyte layer of the semi-solid-state battery can achieve high performance and high safety at the same time by optimizing the interface structure between the positive electrode and the electrolyte.

[0086] Hereinafter, the embodiments of the present invention will be described in more detail by way of examples. However, the embodiments of the present invention are not limited only to these examples.

[0087] Embodiment 1:

[0088] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon nanotubes (CNT), solid electrolyte lithium aluminum titanium phosphate (LATP) and binder polytetrafluoroethylene (PTFE), were weighed according to a mass percentage of 93:2:3:2, wherein LATP is composed of nano-sized and micron-sized particles, and the ratio of nanoparticles to micron particles is 2:1; a through-hole carbon-coated aluminum foil is used as the current collector.

[0089] First, add the three raw materials of NCM811, CNT and LATP into a powerful mixer, stir at a speed of 8000r / min for 60 min at room temperature, and mix the powders to obtain the first powder. Pre-lower the temperature of the stirring tank of the powerful mixer to 5°C, add PTFE binder into the powerful mixer, and stir at a lower speed of 500 r / min for 20 min to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven. The oven temperature is set to 150°C and kept warm for 4 hours to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization. Then add the second powder that has been pre-fiberized and kept warm into the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, ensure that the air flow rate exceeds 300 m / s, achieve full dispersion of each component material and full fiberization of the binder, and obtain the third powder in a fluffy state. The fluffy third powder is then transferred to a multi-stage hot rolling device through a powder metering and conveying device. The rolling temperature is set to 200°C. After multiple hot rolling processes, the third powder is rolled up to obtain a self-supporting electrode membrane.

[0090] The relevant raw materials of the solid electrolyte membrane, including micron-sized solid electrolyte lithium aluminum titanium phosphate (LATP) and binder polytetrafluoroethylene (PTFE), were weighed at a mass percentage of 98:2, and the raw materials were placed in the stirring tank of the powerful mixer. At a temperature of 5°C, the stirring was carried out at a low speed of 500 r / min for 20 min to ensure that PTFE was evenly dispersed in the solid electrolyte powder to form the fourth powder. The fourth powder was taken out of the stirring tank and placed in a high-temperature oven. The oven temperature was set to 150°C and kept warm for 4 hours. Then, the pre-fiberized and insulated fourth powder was added to the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, the air flow velocity was ensured to exceed 300 m / s to achieve full fiberization of the binder and obtain the fifth powder in a fluffy state. Subsequently, the fluffy fifth powder was transferred to the multi-stage hot rolling equipment through the powder metering and conveying device. The rolling temperature was set to 200°C. After multiple hot rolling, it was rolled up to obtain a self-supporting solid electrolyte membrane.

[0091] The solid electrolyte membrane is stacked on top and the electrode membrane is stacked on the bottom. The electrolyte layer and the electrode layer are tightly combined and integrated into one by rolling with hot rolling laminating equipment to obtain an integrated composite positive electrode membrane. Subsequently, the rolled integrated composite positive electrode membrane is rolled and laminated with the through-hole carbon-coated aluminum foil that has been finely treated by chemical or physical rolling equipment to finally obtain an integrated high-load composite positive electrode sheet. Finally, an array-type vertical channel structure is precisely constructed on the solid electrolyte layer and the electrode membrane layer through an advanced laser pore-making process. The obtained integrated composite positive electrode sheet, negative electrode sheet and electrolyte are assembled to evaluate the electrochemical performance of the battery cell.

[0092] This embodiment provides an integrated composite positive electrode sheet with a solid electrolyte layer, including the above-mentioned electrode membrane, solid electrolyte membrane and through-hole carbon-coated aluminum foil, and the above-mentioned membrane and carbon-coated aluminum foil are hot-pressed and composited into one by hot rolling equipment.

[0093] Embodiment 2:

[0094] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon nanotubes (CNT), solid electrolyte lithium aluminum titanium phosphate (LATP) and binder polytetrafluoroethylene (PTFE), are weighed according to a mass percentage of 90:2:5:3, wherein LATP is composed of nano-sized and micron-sized particles, and the ratio of nanoparticles to micron particles is 3:2; a through-hole carbon-coated aluminum foil is used as the current collector.

[0095] First, add the three raw materials of NCM811, CNT and LATP into a powerful mixer, stir at a speed of 10000r / min for 30 min at room temperature, and mix the powders to obtain the first powder. Pre-lower the temperature of the stirring tank of the powerful mixer to 5°C, add PTFE binder into the powerful mixer, and stir at a lower speed of 500 r / min for 20 min to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven. The oven temperature is set to 150°C and kept warm for 4 hours to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization. Then add the second powder that has been pre-fiberized and kept warm into the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, ensure that the air flow rate exceeds 300 m / s, achieve full dispersion of each component material and full fiberization of the binder, and obtain the third powder in a fluffy state. The fluffy third powder is then transferred to a multi-stage hot rolling device through a powder metering and conveying device. The rolling temperature is set to 200°C. After multiple hot rolling processes, the third powder is rolled up to obtain a self-supporting electrode membrane.

[0096] The relevant raw materials of the solid electrolyte membrane, including micron-sized solid electrolyte lithium aluminum titanium phosphate (LATP) and binder polytetrafluoroethylene (PTFE), were weighed at a mass percentage of 98:2, and the raw materials were placed in the stirring tank of the powerful mixer. At a temperature of 5°C, the stirring was carried out at a low speed of 500 r / min for 20 min to ensure that PTFE was evenly dispersed in the solid electrolyte powder to form the fourth powder. The fourth powder was taken out of the stirring tank and placed in a high-temperature oven. The oven temperature was set to 150°C and kept warm for 4 hours. Then, the pre-fiberized and insulated fourth powder was added to the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, the air flow velocity was ensured to exceed 300 m / s to achieve full fiberization of the binder and obtain the fifth powder in a fluffy state. Subsequently, the fluffy fifth powder was transferred to the multi-stage hot rolling equipment through the powder metering and conveying device. The rolling temperature was set to 200°C. After multiple hot rolling, it was rolled up to obtain a self-supporting solid electrolyte membrane.

[0097] The solid electrolyte membrane is stacked on top and the electrode membrane is stacked on the bottom. The electrolyte layer and the electrode layer are tightly combined and integrated into one by rolling with hot rolling laminating equipment to obtain an integrated composite positive electrode membrane. Subsequently, the rolled integrated composite positive electrode membrane is rolled and laminated with the through-hole carbon-coated aluminum foil that has been finely treated by chemical or physical rolling equipment to finally obtain an integrated high-load composite positive electrode sheet. Finally, an array-type vertical channel structure is precisely constructed on the solid electrolyte layer and the electrode membrane layer through an advanced laser pore-making process. The obtained integrated composite positive electrode sheet, negative electrode sheet and electrolyte are assembled to evaluate the electrochemical performance of the battery cell.

[0098] This embodiment provides an integrated composite positive electrode sheet with a solid electrolyte layer, including the above-mentioned electrode membrane, solid electrolyte membrane and through-hole carbon-coated aluminum foil, and the above-mentioned membrane and carbon-coated aluminum foil are hot-pressed and composited into one by hot rolling equipment.

[0099] Comparative Example 1:

[0100] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive agent (CNT), solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 93:2:3:2, of which LATP was a micron-sized powder. First, the three raw materials, NCM811, CNT and LATP, were added to a powerful mixer and stirred at a speed of 8000 r / min for 60 min at room temperature. The powders were mixed evenly to obtain the first powder. The temperature of the stirring tank was lowered to 5°C in advance, and the PTFE binder was added to the mixer. The mixture was stirred at a lower speed of 500 r / min for 20 min to ensure that the PTFE was evenly dispersed in the first powder to form the second powder. The second powder was taken out of the stirring tank and placed in a high-temperature oven at a temperature of 150°C for 4 h to pre-fiberize the binder and achieve the transformation of the crystal form, which was conducive to the subsequent full fiberization to obtain the third powder. Then, the third powder is added to the supersonic airflow mill. By controlling the compressed air flow rate and pressure, the airflow speed is ensured to exceed 300 m / s, so as to achieve full dispersion of each component material and full fiberization of bonding, and obtain fluffy powder. Finally, the fluffy powder is transferred to the multi-stage hot rolling equipment through the powder metering and conveying device. The rolling temperature is 200 ° C. After multiple hot rolling, the self-supporting electrode membrane is obtained by winding. The above-mentioned positive electrode membrane is hot-pressed and composited to the carbon-coated aluminum foil by the hot rolling equipment to prepare the positive electrode sheet. The obtained composite positive electrode sheet, negative electrode sheet, diaphragm and electrolyte are assembled, and the electrochemical performance and safety performance of the battery cell are evaluated.

[0101] Comparative Example 2:

[0102] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive agent (SP), solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 93:2:3:2, of which LATP was a micron-sized powder. First, the three raw materials, NCM811, CNT and LATP, were added to a powerful mixer and stirred at a speed of 8000 r / min for 60 min at room temperature. The powders were mixed evenly to obtain the first powder. The temperature of the stirring tank was lowered to 5°C in advance, and the PTFE binder was added to the mixer. The mixture was stirred at a lower speed of 500 r / min for 20 min to ensure that the PTFE was evenly dispersed in the first powder to form the second powder. The second powder was taken out of the stirring tank and placed in a high-temperature oven at a temperature of 150°C for 4 h to pre-fiberize the binder and achieve the transformation of the crystal form, which was conducive to the subsequent full fiberization to obtain the third powder. Then, the third powder is added to the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, the airflow speed is ensured to exceed 300 m / s, so as to achieve full dispersion of each component material and full fiberization of bonding, and obtain fluffy powder. Finally, the fluffy powder is transferred to the multi-stage hot rolling equipment through the powder metering and conveying device. The rolling temperature is 200 ° C. After multiple hot rolling, the self-supporting electrode membrane is obtained by winding. The above-mentioned positive electrode membrane is hot-pressed and composited to ordinary carbon-coated aluminum foil by hot rolling equipment. The obtained composite positive electrode sheet, negative electrode sheet, diaphragm and electrolyte are assembled, and the electrochemical performance and safety performance of the battery cell are evaluated.

[0103] Comparative Example 3:

[0104] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon nanotubes (CNT), solid electrolyte lithium aluminum titanium phosphate (LATP) and binder polytetrafluoroethylene (PTFE), were weighed according to a mass percentage of 93:2:3:2, wherein LATP is composed of nano-sized and micron-sized particles, and the ratio of nanoparticles to micron particles is 2:1; ordinary carbon-coated aluminum foil is used as the current collector.

[0105] First, add the three raw materials of NCM811, CNT and LATP into a powerful mixer, stir at a speed of 8000r / min for 60 min at room temperature, and mix the powders to obtain the first powder. Pre-lower the temperature of the stirring tank of the powerful mixer to 5°C, add PTFE binder into the powerful mixer, and stir at a lower speed of 500 r / min for 20 min to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven. The oven temperature is set to 150°C and kept warm for 4 hours to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization. Then add the second powder that has been pre-fiberized and kept warm into the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, ensure that the air flow rate exceeds 300 m / s, achieve full dispersion of each component material and full fiberization of the binder, and obtain the third powder in a fluffy state. The fluffy third powder is then transferred to a multi-stage hot rolling device through a powder metering and conveying device. The rolling temperature is set to 200°C. After multiple hot rolling processes, the third powder is rolled up to obtain a self-supporting electrode membrane.

[0106] The relevant raw materials of the solid electrolyte membrane, including micron-sized solid electrolyte lithium aluminum titanium phosphate (LATP) and binder polytetrafluoroethylene (PTFE), were weighed at a mass percentage of 98:2, and the raw materials were placed in the stirring tank of the powerful mixer. At a temperature of 5°C, the stirring was carried out at a low speed of 500 r / min for 20 min to ensure that PTFE was evenly dispersed in the solid electrolyte powder to form the fourth powder. The fourth powder was taken out of the stirring tank and placed in a high-temperature oven. The oven temperature was set to 150°C and kept warm for 4 hours. Then, the pre-fiberized and insulated fourth powder was added to the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, the air flow velocity was ensured to exceed 300 m / s to achieve full fiberization of the binder and obtain the fifth powder in a fluffy state. Subsequently, the fluffy fifth powder was transferred to the multi-stage hot rolling equipment through the powder metering and conveying device. The rolling temperature was set to 200°C. After multiple hot rolling, it was rolled up to obtain a self-supporting solid electrolyte membrane.

[0107] The solid electrolyte membrane is stacked on top and the electrode membrane is stacked on the bottom. The electrolyte layer and the electrode layer are tightly combined and integrated into one by rolling through the hot rolling laminating equipment to obtain an integrated composite positive electrode membrane. Subsequently, the rolled integrated composite positive electrode membrane is rolled and laminated with the chemically or physically finely treated through-hole carbon-coated aluminum foil by hot rolling laminating equipment to finally obtain an integrated high-load composite positive electrode sheet.

[0108] This embodiment provides an integrated composite positive electrode sheet with a solid electrolyte layer, including the above-mentioned electrode membrane, solid electrolyte membrane and through-hole carbon-coated aluminum foil, and the above-mentioned membrane and carbon-coated aluminum foil are hot-pressed and composited into one by hot rolling equipment.

[0109] Performance Test:

[0110] The battery electrodes prepared in Examples 1-2 and Comparative Examples 1-3 were tested using the same testing equipment and testing standards to conduct electrode resistance testing, peel strength testing, and electrochemical performance testing. The specific testing methods are as follows:

[0111] Electrode piece resistance test: It is carried out in a electrode piece resistance meter. At room temperature of 25°C and air humidity of -40°C dew point, the prepared battery electrode is placed on the resistance meter table to make its surface flat. The pressure gauge is adjusted to fix the test sample to ensure good contact between the probe and the sample to obtain the resistance value of the electrode.

[0112] Peel strength test: It is carried out in a peel force tester. At room temperature of 25°C and air humidity of -40°C dew point, one side of the prepared battery electrode current collector is adhered to the working panel with a test double-sided tape, and the active material surface and the peel force tester are connected with a test tape. The peeling speed is 60 mm / min, the peeling angle is 180°, and the peeling force is tested and recorded.

[0113] Electrochemical performance test: The dry-process integrated composite positive electrode sheet, graphite negative electrode and electrolyte are assembled into a button battery, and the capacity of the dry-process composite positive electrode sheet is evaluated at a charge rate of 0.1 C and a discharge rate of 0.1 C at 25°C. Each embodiment and comparative example is cycled 300 times at a charge rate of 0.2 C and a discharge rate of 0.5 C at 25°C, and the battery capacity before and after the cycle is recorded, and the capacity retention rate is calculated. At 25°C, the button battery is charged and discharged at different rates, and the discharge capacity and specific capacity at each rate are recorded, and the capacity retention rate at each rate is calculated. The integrated composite positive electrode sheet, graphite negative electrode and electrolyte are assembled into a soft-pack battery, and a needle puncture test is performed to evaluate the safety performance of the battery.

[0114] Refer to the instruction manual Figure 4-8 , Figure 4 The specific capacity-voltage curves of Example 1 and Comparative Example 1 are shown in FIG. Figure 4It can be seen that under the same voltage range and load, Example 1 has a higher discharge specific capacity, up to 208.4 mAh / g, while the discharge specific capacity of Comparative Example 1 is only 196.7 mAh / g, indicating that the positive electrode material in Example 1 has a higher capacity. Under the same specific capacity, Example 1 can provide higher energy output and improve the overall energy density of the battery, and is suitable for applications with high energy density requirements.

[0115] Figure 5 is the cycle performance curve of Example 1 and Comparative Example 1, from Figure 5 It can be seen that under the same surface loading, the capacity retention rate of Example 1 is still as high as 98.1% after 60 cycles, while the capacity retention rate of Comparative Example 1 is only 93.9%, indicating that the battery of Example 1 has a higher cycle life.

[0116] Figure 6 The high surface capacity electrode prepared by the process of Example 1 was subjected to cycle performance testing and it was found that the surface capacity was as high as 8.5 mAh / cm 2 The battery assembled with the integrated composite positive electrode can be charged and discharged normally, and the capacity retention rate is still as high as 97.6% after 40 cycles. This shows that the array-type through-hole structure constructed on the integrated composite positive electrode connects the efficient and continuous ion and electron transmission network constructed inside, which can solve the problem of long electron and ion transmission paths and slow conduction in thick electrodes, and improve the battery rate charging and discharging performance and the specific capacity of active materials.

[0117] Figure 7 It is a comparison of the discharge capacity retention rates of Example 1 and Comparative Example 1 at different discharge rates (C rates) (XC / 0.1C). The discharge specific capacity of Example 1 at each discharge rate is higher than that of Comparative Example 1, especially at high rate discharge (such as 1C and 2C), the advantage of Example 1 is more obvious. Example 1 has a stronger capacity retention ability under high rate discharge conditions, which shows that its electrode material can function more effectively at high rates. The capacity of Comparative Example 1 decreases faster at high rate discharge, showing poor high rate discharge performance. Therefore, Example 1 has higher application value and competitiveness in practical applications, especially in occasions requiring high rate discharge, such as power tools and electric vehicles.

[0118] Figure 8 (a) is a graph showing the temperature and voltage curve of the battery cell in the acupuncture test of Example 1. Figure 8(b) is the temperature and voltage curve of the cell in the needle puncture test of Example 1. The composite positive electrode sheet prepared in Example 1 and Comparative Example 1 is assembled into a soft-pack cell with a graphite negative electrode sheet and an electrolyte, and a needle puncture safety test is performed on it. It can be clearly seen that after the soft-pack cell of Example 1 is punctured by a steel needle, the voltage changes slightly and then recovers to about 4.0V, and the temperature at the center of the cell is 30°C. In contrast, after the needle puncture, the voltage of Comparative Example 1 drops to 0V instantly, the positive and negative electrodes are directly short-circuited, and the cell temperature rises suddenly to 450°C, and the cell catches fire and explodes. It shows that the solid electrolyte layer of Example 1 can well improve the safety performance of the cell and isolate the contact between the positive and negative electrodes, which is crucial to prevent thermal runaway of the battery and improve battery safety. The voltage of Example 1 remains stable throughout the needle puncture test, with almost no fluctuations. The battery can continue to provide a stable voltage output during operation to ensure the normal operation of the equipment. The voltage of Comparative Example 1 drops sharply in a short period of time, indicating that an internal short circuit has occurred inside the battery, the battery has failed, and cannot continue to be used.

[0119] The examples 1-2 and comparative examples 1-3 were tested according to the above test method to obtain the data in Table 1:

[0120] Table 1

[0121] Group Electrode sheet resistance (Ω·cm) Peel strength (N / m) 0.1C discharge specific capacity (mAh / g) 1C discharge specific capacity (mAh / g) Capacity retention rate after 200 cycles % Example 1 14.8 40.4 208.4 189.6 93.1 Example 2 16.3 42.7 206.1 185.5 92.4 Comparative Example 1 26.7 22.7 196.7 169.8 81.5 Comparative Example 2 295.1 20.8 191.7 86.3 35.7 Comparative Example 3 46.1 21.3 192.3 154.8 78.9

[0122] From Table 1 we can see that:

[0123] Pole sheet resistance: The pole sheet resistances of Examples 1-2 are 14.8Ω·cm and 16.3Ω·cm, respectively, which are significantly lower than 26.7Ω·cm, 295.1Ω·cm and 46.1Ω·cm of Comparative Examples 1-3. This indicates that Examples 1-2 have better conductivity and lower resistance, which helps to improve the overall efficiency of the battery.

[0124] Peel strength: The peel strengths of Examples 1-2 are 40.4 N / m and 42.7 N / m, respectively, which are much higher than 22.7 N / m, 20.8 N / m, and 21.3 N / m of Comparative Examples 1-3. This indicates that the bonding strength between the electrode and the current collector of Examples 1-2 is higher, the structural stability is better, and it helps to improve the mechanical stability and life of the battery.

[0125] 0.1C discharge specific capacity: The 0.1C discharge specific capacity of Examples 1-2 is 208.4 mAh / g and 206.1 mAh / g, respectively, which is higher than 196.7 mAh / g to 192.3 mAh / g of Comparative Examples 1-3. This shows that Examples 1-2 achieve a higher utilization rate of active materials in terms of material selection and electrode design.

[0126] 1C discharge specific capacity: The 1C discharge specific capacity of Examples 1-2 is 189.6 mAh / g and 185.5 mAh / g, respectively, which is significantly better than 169.8 mAh / g, 86.3 mAh / g and 154.8 mAh / g of Comparative Examples 1-3. This shows that under high-rate discharge conditions, the electrode of Examples 1-2 can still maintain a high utilization rate of active materials and reduce the polarization effect.

[0127] Capacity retention rate after 200 cycles: The capacity retention rates of Examples 1-2 are 93.1% and 92.4%, respectively, which are much higher than 81.5%, 35.7% and 78.9% of Comparative Examples 1-3. This shows that the batteries of Examples 1-2 can still maintain most of their initial capacity after 200 cycles, showing excellent cycle stability.

[0128] In summary, Examples 1-2 show superior performance in terms of resistance, peel strength, discharge specific capacity and cycle life, and are significantly better than Comparative Examples 1-3.

[0129] The present invention prepares oxide solid electrolyte film through dry process, and uses precision rolling to achieve close compound with high-load electrode membrane, which reduces interface resistance and improves the overall safety of the battery; introduces laser pore-making technology to construct array through-hole structure, optimizes pore layout, improves porosity, accelerates electrolyte infiltration and ion transmission efficiency; the positive electrode layer integrates micron and nano-scale solid electrolyte particles, and improves lithium ion migration rate through dual particle size strategy. Highly conductive carbon materials are used to construct efficient conductive networks and enhance electron transmission efficiency; special array through-hole carbon-coated aluminum foil current collectors further enhance the electrochemical performance of the battery by enhancing binding force and increasing active sites.

[0130] The above is only an embodiment of the present invention, and the common sense such as the known specific structure and characteristics in the scheme is not described in detail here. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the attached claims rather than the above description, so it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any figure mark in the claims should not be regarded as limiting the claims involved.

Claims

1. A method for preparing an integrated composite positive electrode sheet with a solid electrolyte layer, characterized in that: The preparation method comprises the following steps: Step 1: premixing the conductive carbon material, oxide solid electrolyte particles of various particle sizes, and the positive electrode active material in a certain proportion to obtain a mixed material, and using a high-speed dispersion process to obtain a uniformly mixed first powder; Step 2: adding a certain amount of binder to the first powder, dispersing the binder and the first powder under low temperature and low speed conditions to uniformly mix the binder and the first powder to obtain a second powder; Step 3: heat-insulating the second powder at a certain temperature to obtain a pre-fiberized second powder; Step 4: treating the heat-insulated second powder with a supersonic airflow to fiberize the binder in the second powder, and uniformly dispersing the conductive carbon material and oxide solid electrolyte particles of various particle sizes in the second powder, coating them on the outer surface of the positive electrode active material particles and incorporating them into the fiberized binder together, to obtain a third powder; Step 5: subjecting the third powder to a multi-stage hot roller pressing process to obtain an electrode membrane; Step 6: premixing the binder and the oxide solid electrolyte particles in a certain proportion, dispersing them under low temperature and low speed conditions to obtain a fourth powder, and treating the fourth powder according to steps 3-5 to obtain a solid electrolyte membrane; Step 7: stacking the electrode membrane and the solid electrolyte membrane in a certain order and performing hot rolling treatment to obtain an integrated composite positive electrode membrane; Step 8: stacking the integrated composite positive electrode film and the carbon-coated aluminum foil current collector and performing a hot rolling process, constructing channel holes on the integrated composite positive electrode sheet after hot rolling, and obtaining an integrated composite positive electrode sheet with a solid electrolyte layer; The oxide solid electrolytes of various particle sizes in step 1 include at least two types of micron particles and nanoparticles; the oxide solid electrolytes in steps 1 and 6 include one or more of perovskite oxide solid electrolytes, garnet oxide solid electrolytes, and NASICON oxide solid electrolytes; In step 8, laser pore making is performed and vertical channel holes are constructed from one side of the integrated composite positive electrode sheet having the solid electrolyte membrane toward the electrode membrane in an array distribution manner.

2. The method for preparing an integrated composite positive electrode sheet with a solid electrolyte layer according to claim 1, characterized in that: The depth of the channel hole is the sum of the thickness of the solid electrolyte membrane and the electrode membrane.

3. The method for preparing an integrated composite positive electrode sheet with a solid electrolyte layer according to claim 1, characterized in that: In step 6, the amount of the binder added is 1-7wt% of the mass of the solid electrolyte membrane, and the amount of the oxide solid electrolyte particles added is 93-99wt% of the mass of the solid electrolyte membrane.

4. The method for preparing an integrated composite positive electrode sheet with a solid electrolyte layer according to claim 1, characterized in that: In step 7, the solid electrolyte membrane is stacked and rolled in the order of being located above the electrode membrane. In step 8, the integrated composite positive electrode membrane is stacked and rolled with one side of the electrode membrane being in contact with the carbon-coated aluminum foil current collector.

5. The method for preparing an integrated composite positive electrode sheet with a solid electrolyte layer according to claim 1, characterized in that: In step 8, an array-type through-hole structure is provided on the carbon-coated aluminum foil current collector.

6. An integrated composite positive electrode sheet with a solid electrolyte layer, characterized in that: The integrated composite positive electrode sheet with a solid electrolyte layer is prepared by the preparation method described in any one of claims 1 to 5; it includes an integrated composite positive electrode membrane and an array-type through-hole carbon-coated aluminum foil current collector close to the integrated composite positive electrode membrane; the integrated composite positive electrode membrane includes a solid electrolyte membrane and an electrode membrane, and the solid electrolyte membrane and the array-type through-hole carbon-coated aluminum foil current collector are respectively composited on both sides of the electrode membrane.

7. The integrated composite positive electrode sheet with a solid electrolyte layer according to claim 6, characterized in that: The thickness of the solid electrolyte membrane is 10-60 μm.

8. The integrated composite positive electrode sheet with a solid electrolyte layer according to claim 6, characterized in that: The thickness of the integrated composite positive electrode plate is 30-500 μm, and the aperture of the channel hole of the integrated composite positive electrode plate is 5-500 μm.

Citation Information

Patent Citations

  • Method for preparing electrode membrane of lithium ion battery by dry method

    CN115579458A

  • Composite electrode plate, preparation method thereof and lithium ion battery

    CN117117101A

  • Collector material, and method of manufacturing the same

    JP2008283152A

  • All-solid-state lithium-ion secondary battery

    WO2014132333A1